Relação entre as características do CEO e o gerenciamento de resultados - Sprenger, Kélim Bernardes (Universidade do Vale do Rio dos Sinos, 2016)
Considering that the outcome of a company affects the investors’ decision in the market and in the company’s management, some managers may use the discretion in the measurement and accounting disclosure process to manage the results. To further understand the circumstances linked to this practice in Brazil, this study aimed to analyze the relationship between the characteristics of the Chief Executive Officer (CEO) and earnings management in companies listed on the BM&FBovespa. To achieve this study, each company CEO’s information was collected, such as age, gender, previous experience, level of education and area, as well as their form of election and positions held by them in the period 2010-2015, through the Formulário de Referência (reference form). In order to detect earnings management, Jones model (1991) and Jones Modified model (1995) were used, which residues represent discretionary accruals, considered in the literature as earnings management’ proxy. Thus, for each company and each year, discretionary accruals were estimated and considered as a dependent variable in a multiple regression designed to establish a relationship between the CEO characteristics and earnings management. Data were organized and estimated at pool of cross-section. The main results indicate that the higher the payment for performance measurement (MRD) of the CEO, the lower the use of discretionary accruals. Consequently, there will be a lower level of earnings management. It was also found that there is a relationship between the age and gender of the CEO with the management results, indicating that the higher the age of the CEO, the lower the earnings management, and that men make more use of discretionary accruals. It also identified that companies with foreign stock control are less related to earnings management.
Keywords: Gerenciamento de resultados; CEO; Accruals discricionários; Earnings management; Discretionary accruals; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis